(untitled) (Journal of Information Technologies in Education (ITE), 2015)
The widespread introduction of electronic educational resources in the educational process requires the development of a scientific basis for all aspects related to their creation and use. These modern means are designed not just to convey to learners the required course material, but also to create conditions for its most effective study. This is possible in conditions of reasonable approach to the presentation of educational material on the screen. The article is devoted to consideration of the problem of presenting educational material in electronic educational resources. Visuals are powerful didactic tool that enhances the perception and understanding of educational information. Particular attention is paid to the use of such a powerful medium like video. Investigated the role and importance of video in the learning process, their educational opportunities and benefits. Shows types of video and their use in electronic educational resources. Grounded requirements for training videos. The recommendations are given on the use of video in combination with other media in electronic educational resources. Adduced the example a real electronic multimedia educational resource and shows the possibility of using video.